Prevalence of Nocturia in Taiwanese Women Aged 20-59 Years - Ching-Hung Hsieh; Hsing-Yu Chen; Chun-Sen Hsu; Shao-Tung Chang; Chien-Dai Chiang (Elsevier, 2007)
Objective: To estimate the prevalence of nocturia in Taiwanese women aged 20-59 years. Materials and Methods: A random sample of 4,549 women within the age range was selected by a multistage sampling design. Face-to-face visits with 3,537 women were completed by well-trained professional interviewers. Nocturia, according to the definition of the International Continence Society, and its associated problems were evaluated and, concurrently, variables of medical histories and sociodemography were recorded. Results: The response rate was 77.8%, and a total of 930 of 3,521 women reported having had nocturia, producing a prevalence of nocturia of 26.4%, with 16 not answering the question about nocturia. For those who had nocturia, 88.9% of the interviewees reported ≤ 2 voids per night and 1.6% of these women reported having to void ≥ 5 times per night. Conclusion: Nocturia is a common condition among Taiwanese women, especially among the elderly. Its prevalence is significantly related to age. Treatment of this condition in this patient population can both improve their quality of life and reduce the risk of deterioration in their general state of health.